Chemical Modeling of Orion Nebula Cluster Disks: Evidence for Massive, Compact Gas Disks with Interstellar Gas-to-dust Ratios - Boyden, Ryan D.; Eisner, Josh A. (The Astrophysical journal, 2023)
The stellar cluster environment is expected to play a central role in the evolution of circumstellar disks. We use thermochemical modeling to constrain the dust and gas masses, disk sizes, UV and X-ray radiation fields, viewing geometries, and central stellar masses of 20 class II disks in the Orion Nebula Cluster (ONC). We fit a large grid of disk models to 350 GHz continuum, CO J = 3 − 2, and HCO + J = 4 − 3 Atacama Large Millimeter/submillimeter Array observations of each target, and we introduce a procedure for modeling interferometric observations of gas disks detected in absorption against a bright molecular cloud background. We find that the ONC disks are massive and compact, with typical radii <100 au, gas masses ≥10 −3 M ⊙ , and gas-to-dust ratios ≥100. The interstellar‐medium‐like gas-to-dust ratios derived from our modeling suggest that compact, externally irradiated disks in the ONC are less prone to gas-phase CO depletion than the massive and extended gas disks that are commonly found in nearby low-mass star-forming regions. The presence of massive gas disks indicates that external photoevaporation may have only recently begun operating in the ONC; though it remains unclear whether other cluster members are older and more evaporated than the ones in our sample. Finally, we compare our dynamically derived stellar masses with the stellar masses predicted from evolutionary models and find excellent agreement. Our study has significantly increased the number of dynamical mass measurements in the mass range ≤0.5 M ⊙ , demonstrating that the ONC is an ideal region for obtaining large samples of dynamical mass measurements toward low-mass M-dwarfs.